Effect of Petroleum Hydrocarbons on Microbial Populations in an Arctic Lake - Jordan, M.J.; Hobbie, J.E.; Peterson, B.J. (ARCTIC, 1978)
A sea-curtain enclosed section of a lake 240 km south of Prudhoe Bay, Alaska was exposed to Prudhoe crude oil in July 1976. One year following exposure to the oil, no significant differences were detected between the waters or sediments of the oiled versus control area in rates of turnover of glucose. Total numbers of bacteria were slightly higher in oiled than in control waters. There were no differences in numbers of sediment bacteria. Rates of uptake of hexadecane and napthalene by sediment microbes were not linear with time. Hexadecane was taken up sooner and faster than was napthalene. In 0 some incubations, significantly (88 - 95% probability level) greater rates of hydrocarbon uptake were measured for oiled than for control sediments. Only incorporated, not mineralized, hydrocarbons were measured due to methodological problems. Several methods of using 14C-labelled hydrocarbons in a field situation are presented.